2011
DOI: 10.1007/s00464-011-1937-1
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal endoscopic myotomy for achalasia: recognizing potential pitfalls before clinical application

Abstract: The TEEM procedure is technically feasible. Due to the morbidity encountered in the first three pigs, the reported technique was modified to include a slimmer endoscope, a shorter tunnel, and a partial-thickness myotomy. These changes together with an understanding of the pitfalls involved in this procedure led to successful results for the next three pigs. Nevertheless, the authors believe that TEEM is not yet ready for prime time. Perfection of the technique and development of dedicated instruments are manda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Reports of using fibrin sealant to repair an esophageal penetration at the time of endoscopic myotomy as confirmed on repeat endoscopy [259] and using sutures and fibrin sealant to close the mucosa after endoscopic cricopharyngeal myotomy as confirmed at repeat esophagram [260] were published. A laboratory study in pigs ( n = 6) supported the use of fibrin sealant to close the mucosa in a model of transesophageal, endoscopic, esophagomyotomy (TEEM), although the authors suggested that the procedure was not yet perfected enough for use in humans [261]. A rat model [262] demonstrated that in control versus fibrin sealant coated equine collagen patch treated animals, respectively, there was an increase in burst strength at esophagogastric anastomoses on days 0 and 3 (55.1 ± 4.6 versus 102.4 ± 7.3 mmHg, P < 0.010 and 19.7 ± 3.3 versus 34.6 ± 4.9 mmHg, P < 0.050), although no significant differences were noted in burst strength at days 5 and 7 (60.9 ± 18.2 versus 53.4 ± 6.6 mmHg, P = 0.690; and 118.8 ± 20.2 versus 97.2 ± 8.3 mmHg, P = 0.374).…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 99%
“…Reports of using fibrin sealant to repair an esophageal penetration at the time of endoscopic myotomy as confirmed on repeat endoscopy [259] and using sutures and fibrin sealant to close the mucosa after endoscopic cricopharyngeal myotomy as confirmed at repeat esophagram [260] were published. A laboratory study in pigs ( n = 6) supported the use of fibrin sealant to close the mucosa in a model of transesophageal, endoscopic, esophagomyotomy (TEEM), although the authors suggested that the procedure was not yet perfected enough for use in humans [261]. A rat model [262] demonstrated that in control versus fibrin sealant coated equine collagen patch treated animals, respectively, there was an increase in burst strength at esophagogastric anastomoses on days 0 and 3 (55.1 ± 4.6 versus 102.4 ± 7.3 mmHg, P < 0.010 and 19.7 ± 3.3 versus 34.6 ± 4.9 mmHg, P < 0.050), although no significant differences were noted in burst strength at days 5 and 7 (60.9 ± 18.2 versus 53.4 ± 6.6 mmHg, P = 0.690; and 118.8 ± 20.2 versus 97.2 ± 8.3 mmHg, P = 0.374).…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 99%
“…However, the upper mediastinum is difficult to approach using the standard laparoscopic technique. Third, POEM can be performed to selectively dissect the inner circular muscle fiber whereas full-thickness laparoscopic myotomy increase the possibility of vagal nerve or adjacent structure injury and reflux esophagitis 15. High LES pressure decreases to a normal range without any incision of the outer longitudinal muscle layer 8.…”
Section: Discussionmentioning
confidence: 99%
“…Some say that the pig esophagus is so fragile and muscularis propria is movable that it is not a good model to train esophageal endoscopic submucosal dissection 18. Nevertheless, porcine esophagus would be a good substitute for training POEM due to its anatomic similarity, and actually it has been widely used to study and train POEM 7,15,19…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de sus ventajas, posee inconvenientes: en primer lugar, es una técnica reciente sin resultados a largo plazo, se requiere anestesia general y complejos preparativos para realizar el abordaje endoscópico, el tiempo es similar al de la miotomía laparoscópica (100 min), y no se asocia a procedimiento antirreflujo, lo que podría inducir un mayor potencial de reflujo gastroesofágico que en la técnica laparoscópica convencional 13 .…”
Section: Discussionunclassified